2014
DOI: 10.2188/jea.je20130168
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Risk of Colorectal Cancer: The Japan Collaborative Cohort Study

Abstract: BackgroundEpidemiologic studies have reported coffee consumption to be associated with various health conditions. The purpose of this study was to examine the relationship of coffee consumption with colorectal cancer incidence in a large-scale prospective cohort study in Japan.MethodsWe used data from the Japan Collaborative Cohort Study for Evaluation of Cancer Risk (JACC Study). Here, we analyzed a total of 58 221 persons (23 607 men, 34 614 women) followed from 1988 to the end of 2009. During 738 669 person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Five cohort studies (24,25,33,39,40) and nine case-control studies (26)(27)(28)(29)34,35,(41)(42)(43)) met the inclusion criteria. As regards cohort studies (Table 1 and Supplementary Table 1), all reported results for men and women separately (24,25,33,39,40); of these, one additionally reported results for men and women combined (33).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five cohort studies (24,25,33,39,40) and nine case-control studies (26)(27)(28)(29)34,35,(41)(42)(43)) met the inclusion criteria. As regards cohort studies (Table 1 and Supplementary Table 1), all reported results for men and women separately (24,25,33,39,40); of these, one additionally reported results for men and women combined (33).…”
Section: Resultsmentioning
confidence: 99%
“…As regards cohort studies (Table 1 and Supplementary Table 1), all reported results for men and women separately (24,25,33,39,40); of these, one additionally reported results for men and women combined (33). One study showed RRs for colon and rectum combined, but not separated (24); another reported result for colon only (39) and the remaining studies displayed results for both sites combined as well as for colon and rectum separately (25,33,40). In men, one study showed a moderate positive association with colon cancer (25), but the majority of cohort studies observed no association between coffee intake and colon cancer (33,39,40).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations